2006
DOI: 10.1007/s11340-006-9823-9
|View full text |Cite
|
Sign up to set email alerts
|

Study on Deformation of Polycrystalline Aluminum Alloy Using Moiré Interferometry

Abstract: Polycrystalline aluminum alloy is manufactured by annealing, compared to the width of the specimen, the size of the grains can not be omitted, which makes the specimen anisotropic. Under uniaxial tension, the deformation field is inhomogeneous. In this study, moiré interferometry is successfully applied to measure the deformation of the polycrystalline specimen. The experimental results presented the stress versus strain responses of the marked grains in different orientations and different shapes. By using fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The fringe order is -1, -2 and -3 along the opposite of x direction. Furthermore, the displacement field was calculated based on the fringe centerline detection [14]. The displacement distribution of the right part of the U field is shown in Fig.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The fringe order is -1, -2 and -3 along the opposite of x direction. Furthermore, the displacement field was calculated based on the fringe centerline detection [14]. The displacement distribution of the right part of the U field is shown in Fig.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Guo et al [75] recently reported deformation of polycrystalline aluminum alloys using moiré interferometry. They studied a specimen whose grain size was on the same scale as the width of the tensile specimen that was used for loading.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…In the last decades, the optical experimental technique, Moiré Interferometry, has been implemented in many fields, of which the most important are the material characterization [2][3][4], microelectronics devices [5,6], micromechanics [7,8], fracture mechanics [9][10][11], the residual stress [12][13][14], composite materials [15,16] and biomechanics [17,18]. For all these cases the main goal is the global measurement of displacement fields without contact with high resolution and accuracy that the Moiré Interferometry method can offer.…”
Section: Introductionmentioning
confidence: 99%